Identity and Perception of the Sheperds' Profession - Novo, Sabela (2022)
The paper discusses the challenges facing sheep farmers in Portugal, particularly in hiring and retaining shepherds. A qualitative study was conducted based on personal interviews with 65 shepherds in the Trás-os-Montes region to identify their vision of pastoralism, their profession, and their roles. The study found that most shepherds are male and aging, with low educational levels, and livestock production as their main occupation. The main motivations for the profession were to work with animals, lack of better job opportunities, and a source of income. Most shepherds have a positive image of the profession but believe it is not socially valorized, and half do not wish to be followed by their heirs. The paper highlights the importance of linking the public perception of pastoralism with environmental and social values to increase the attractiveness of shepherding as a profession.